2000
DOI: 10.1680/geot.2000.50.2.181
|View full text |Cite
|
Sign up to set email alerts
|

Fall-cone penetration and water content relationship of clays

Abstract: Results of previous studies on using the fall-cone test to determine the plastic limit of soils show that further research is warranted. The present investigation devotes itself to modification of the specimen preparation technique, examination of the relationship between depth of cone penetration and water content, and estimation of the plastic limit using the penetration depth against water content relationship. Specimen rings are made and used to replace the specimen cup so as to facilitate the preparation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(56 citation statements)
references
References 13 publications
0
42
0
Order By: Relevance
“…Feng, 2000 andKoumoto &Houlsby, 2001) is also shown to be an acceptable way to describe fall cone data. If modeled in this way, a higher value of the slope increase is computed owing to the high curvature of the function close to the plastic limit.…”
Section: Strength Values At Plastic Limit Predicted By Critical Statementioning
confidence: 97%
See 1 more Smart Citation
“…Feng, 2000 andKoumoto &Houlsby, 2001) is also shown to be an acceptable way to describe fall cone data. If modeled in this way, a higher value of the slope increase is computed owing to the high curvature of the function close to the plastic limit.…”
Section: Strength Values At Plastic Limit Predicted By Critical Statementioning
confidence: 97%
“…Feng, 2000;Dolinar & Trauner, 2005;Lee & Freeman, 2009). Almost all of these researchers have assumed that the plastic limit is associated with a fixed strength (100 times that at w L ) and then used a strength test (e.g.…”
Section: Strength At Plastic Limitmentioning
confidence: 99%
“…Simply based on analysis of historical data, as the ratio of strengths at the PL and LL varies substantially between soils, these strength-based approaches can only coincidentally give correct PL values, actually measuring what might be termed the plastic strength limit (PL 100 ); that is the water content corresponding to s uFC ¼ 100 Â s uFC(LL) . Fall cone Belviso et al, 1985;Wasti, 1987;Harison, 1988;Feng, 2000Feng, , 2001Feng, , 2004Koumoto & Houlsby, 2001;Sharma & Bora, 2003;Lee & Freeman, 2009;Shimobe, 2010;Sivakumar et al, 2015), steady monotonic penetration (Stone & Phan, 1995;Stone & Kyambadde, 2007), fast-static loading (Sivakumar et al, 2009) and extrusion (Timár, 1974;Whyte, 1982;Medhat & Whyte, 1986;Kayabali & Tufenkci, 2010a, 2010bKayabali, 2011aKayabali, , 2011bKayabali, , 2012Kayabali et al, 2016) approaches for PL determination have all been suggested as alternatives to the standard thread-rolling approach. As mechanical tests, these strength-based approaches are seen by some researchers as means of achieving higher degrees of repeatability and reproducibility of results, although, to date, most fall-cone research has been conducted on well-behaved clay-rich soils that lie above the A-line on the standard plasticity chart.…”
Section: Strength-based Approachesmentioning
confidence: 99%
“…w , PL) for water contents around PL 100 . This has implications for the preparation of the test specimens for fall-cone testing near the PL 100 Whyte, 1982;Wasti & Bezirci, 1986;Harison, 1988;Stone & Phan, 1995;Feng, 2000), in that for many cases sample preparation is difficult and some test specimens are likely not to be saturated, and calls into question the use of Hansbo's equation (1) for non-ductile materials. For PL 100 , PL, the strain-rate dependence and deformation mode of the soil test specimen will be significantly different for water contents between the PL 100 and the PL (i.e.…”
Section: Other Factors Influencing Deduced Atterberg Limit Valuesmentioning
confidence: 99%
“…Although it was originally developed to estimate the strength of remoulded cohesive soils, it became widely used as a standard method of determining the liquid limit of clays (Koumoto & Houlsby, 2001), having already been included in the British, Swedish, Canadian and Japanese standards (Claveveau-Mallet et al, 2012;Feng, 2000;Tanaka et al, 2012).…”
Section: Introductionmentioning
confidence: 99%